Coping with the Chernobyl disaster: a comparision of social effects in two reindeer-herding areas - Beach, Hugh (Rangifer, 1990)
Lapland reindeer herders in the Vilhelmina and Jokkmokk municipalities of Sweden were interviewed in summer, autumn and winter 1987/88. The great variability in nuclear contamination between these areas has occasioned obvious but also unforeseen differences in the social effects for the Sami. The variability of contamination has also been compounded by the variability of compensation policy, variability of expert statements about risk, and also the change in state limits on Bq. concentrations set for meat marketability. This paper will illustrate the broad spectrum of Chernobyl-related social problems and the methods of coping with them.
Keywords: Rangifer tarandus; Sami; Sweden; Lapland; anthropology; social effects; Chernobyl